Characterization of edge turbulence in different states of divertor detachment using reflectometry in the ASDEX Upgrade tokamak. (29th March 2018) - Nikolaeva, V; Guimarais, L; Manz, P; Carralero, D; Manso, M E; Stroth, U; Silva, C; Conway, G D; Seliunin, E; Vicente, J; Brida, D; Aguiam, D; et al.
Abstract: Transport in the scrape-off layer (SOL) depends on the state of divertor detachment. L-mode discharges were analyzed where the state of divertor detachment is varied through a density ramp-up. By means of reflectometry measurements at the low (LFS) and the high field side (HFS), midplane density fluctuations are studied for the first time in ASDEX Upgrade simultaneously at both sides of the tokamak. Radial density fluctuation profiles ( δ n e / n e ) increase with radius in both the HFS and the LFS. It is found that in the SOL density fluctuations at the LFS have about a factor of two larger amplitude than at the HFS in agreement with ballooned transport. Density fluctuations at the LFS show a modest variation with increasing background density resulting mainly from a rise of low frequency components. Experimental results are in good agreement with an enhanced convection of filaments at the LFS at the beginning of outer divertor detachment leading to a flatter SOL density profile. In this phase of the discharge, density fluctuations measured at the HFS far-SOL display a strong increase, which may be associated with the presence of faster filaments originated at the LFS.